Personal reflection - Sehwail, Mahmud (Torture Journal, 2022)
Contribution to the 30th Anniversary of the Torture Journal by Dr. Mahmud Sehwail. The author brings an account of his life trajectory as a psychiatrist born and working in Palestine. The author dives in his early memories, including those of his brother's death, that shaped his character and the way he lives his rejection of occupation and violence. Besides the early institutional beginnings of the TRC Center in Ramallah, the author describes the subtle forms of the daily abuse that a doctor working in Palestine must endure.